Prognosis of nodal micrometastasis in resectable pN0 non-small cell lung cancer - Siwachat, Sophon; Tantraworasin, Apichat; Lertprasertsuke, Nirush; Saeteng, Somcharoen (Frontiers in Oncology, 2025)
BackgroundNodal micrometastasis (NMM) is the presence of a small cluster of tumor cells in a regional lymph node. However, the prognostic value of NMM in resectable NSCLC is still debated.MethodsThis retrospective cohort study at Maharaj Nakorn Chiang Mai Hospital from 2006 to 2017 assesses the prognostic impact of nodal micrometastasis in resectable pN0 NSCLC patients, using immunohistochemistry staining for cytokeratin AE1/AE3, p53, and BerEp4. Patients are categorized into three groups: pN0 without nodal micrometastasis, pN0 with nodal micrometastasis, and pN+. Overall survival is the primary endpoint, with disease-free survival as the secondary endpoint.ResultsOut of 225 patients, 98 had pathological N0 (pN0) status and 127 had pathological N positive (pN+) status. Among pN0 patients, nodal micrometastasis was found in 21 cases (21.43%), distributed as follows: 2 (2.04%) in hilar and interlobar regions (N1), 17 (17.35%) in the mediastinal region (N2), and 2 in both hilar and mediastinal regions (N1+N2) (2.04%).Univariable analysis revealed that male sex and the presence of tumor necrosis increased both the recurrence rate of lung cancer and the mortality rate, whereas larger tumor size, intra-tumoral vascular invasion, and pleural invasion were associated solely with cancer recurrence. However, multivariable analysis showed no statistically significant difference in disease-free survival and overall survival between pN0 patients with and without NMM, with hazard ratios of 0.98 (95% CI: 0.31-3.08, P=0.973) and 1.11 (95% CI: 0.23-5.42, P=0.900), respectively.ConclusionNodal micrometastasis was identified in 21.43% of pN0 resectable NSCLC patients. However, the benefits of NMM detection in resectable cases remain controversial due to conflicting results from retrospective studies. Larger prospective cohort studies are needed to better understand disease prognosis and inform treatment strategies.